2014
DOI: 10.1002/ijc.28884
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional scaling analysis identifies pathological and prognostically relevant profiles of circulating T‐cells in chronic lymphocytic leukemia

Abstract: Antitumor immunity in chronic lymphocytic leukemia (CLL) is hampered by highly dysfunctional T-cells. Although certain T-cell subsets have been reported to be of prognostic significance in this disease, their interplay is complex and it remains incompletely understood which of these subsets significantly drive CLL progression. Here, we determined immunological profiles of 24 circulating T-cell subsets from 79 untreated individuals by multiparametric flow cytometry. This screening cohort included healthy donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Moreover, CD39 þ Tregs are overrepresented in patients with cancer and AIDS [17,32], conditions that require less regulatory activity for healing. Thus, modulating the activity of this The region comprising rs10748643 nucleotide polymorphism (SNP) in the ENTPD1 gene was sequenced and the donors were grouped according to their genotype: A/A, A/G and G/G (n ¼ 5, 7 and 6 donors, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CD39 þ Tregs are overrepresented in patients with cancer and AIDS [17,32], conditions that require less regulatory activity for healing. Thus, modulating the activity of this The region comprising rs10748643 nucleotide polymorphism (SNP) in the ENTPD1 gene was sequenced and the donors were grouped according to their genotype: A/A, A/G and G/G (n ¼ 5, 7 and 6 donors, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…4,7,18 Previous studies in Em-TCL1 mice demonstrated that molecular T-cell defects and subset changes can be modeled in leukemic mice, 28,29,32 but have failed to take full advantage of the availability of different microenvironments. In CLL patients, T-cell defects and associations with aggressive disease/poor outcome have been extensively characterized, 3,4,6,18,[33][34][35][36][37] but have focused largely on PB. However, different organs provide distinct and unique microenvironments for CLL cells, 20,21 and it is not known if the same holds true for T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were performed on a Navios flow cytometer (Beckman Coulter, Krefeld, Germany). The gating strategy has been previously described including raw data sets for this flow cytometry immunoprofiling approach …”
Section: Methodsmentioning
confidence: 99%